(untitled) (Research, Society and Development, 2020)
This work consists of an analysis of the effectiveness of the conversion of fines into environmental services in relation to the payment for environmental fines, specifically regarding the program of conversion of environmental fines, compared to the condemnation to pay only the fines and their collection.Exploratory and explanatory literature review studies were used, as well as normative analysis related to the theme. It was found that the traditional procedure of applying an environmental fine collect less than necessary to repair damage to the environment, in view of the judicial delays and the factor of prescription, representing obstacles to the repair of environmental damage.On the other hand, the possibility of converting a fine into environmental services shows advantages for both the assessed taxpayer and the Public Administration, allowing the formulation of an agreement between the environmental agency and the offender for the full reparation of environmental damage, without the obligation to resort to Judiciary, saving time and resources, providing even greater participation of the offender in environmental projects, resulting in environmental education to prevent future infractions.